Influence of shale‐total organic content on CO2 geo‐storage potential. Issue 17 (9th September 2017) - Arif, Muhammad; Lebedev, Maxim; Barifcani, Ahmed; Iglauer, Stefan
Abstract: Shale CO2 wettability is a key factor which determines the structural trapping capacity of a caprock. However, the influence of shale‐total organic content (TOC) on wettability (and thus on storage potential) has not been evaluated despite the fact that naturally occurring shale formations can vary dramatically in TOC, and that even minute TOC strongly affects storage capacities and containment security. Thus, there is a serious lack of understanding in terms of how shale, with varying organic content, performs in a CO2 geo‐storage context. We demonstrate here that CO2 ‐wettability scales with shale‐TOC at storage conditions, and we propose that if TOC is low, shale is suitable as a caprock in conventional structural trapping scenarios, while if TOC is ultrahigh to medium, the shale itself is suitable as a storage medium (via adsorption trapping after CO2 injection through fractured horizontal wells). Key Points: Shale total organic content (TOC) scales with CO2 wettability Low TOC shales are water‐wet at storage conditions (good for structural trapping) Organic‐rich shales are CO2 ‐wet at storage conditions (good for adsorption trapping)